AT A SNAIL'S PACE: ON THE LIMITED EUROPEANIZATION OF DOMESTIC CONSULTATION PRACTICES. (25th March 2013) - BRAUN, CAELESTA; VAN DEN BERG, CASPAR
<x xml:space="preserve">Abstract</x> Consultation of major interest groups is a widespread administrative practice in many EU member states. To date it is unclear, however, how advancing European integration influences domestic consultation practices. This article examines the impact of European integration on domestic consultation practices by conceptualizing how the underlying rationales of government–interest group interactions and the level of involvement of interest groups are affected by European integration. The study draws on original survey data on senior civil servants in Britain and the Netherlands to empirically examine these effects. European integration is related in a limited way to domestic consultation practices, both in Britain and the Netherlands. This small but significant effect is mostly observed during the process of domestic preference formulation in EU‐level policy making. Our findings suggest that intra‐organizational processes, for example organizational routines and task‐specialization, potentially play a greater role than has thus far been appreciated in Europeanization studies.